Navigating barriers to decarbonisation of UK’s aviation sector through green hydrogen: a multi-scale perspective - Mirzania, Pegah; Balta-Ozkan, Nazmiye; Rothe, Henrik; Gratton, Guy (MDPI, 2025)
Aviation is widely recognised as one of the most carbon-intensive modes of transport and among the most challenging sectors to decarbonise. The use of green hydrogen (H2) in airside operations can help reduce emissions from air transport. While the pace and scalability of technology development, including H2-powered and ground support equipment, will be key factors, other financial, regulatory, legal, organisational, behavioural, and societal issues must also be considered. This paper investigates the key opportunities and challenges of using H2 in the aviation industry through eleven semi-structured interviews and a virtual expert workshop (N = 37) with key aviation industry stakeholders and academia. The results indicate that, currently, decarbonisation of the aviation sector faces several challenges, including socio-technical, techno-economic, and socio-political challenges, with socio-technical challenges being the most prominent barrier. This study shows that decarbonisation will not occur until the UK government is ready to have all the required infrastructure and capacity in place. Governments can play a significant role in directing the necessary ‘push’ and ‘pull’ to develop and promote zero-carbon emission aircraft in the marketplace and ensure safe implementation.
Keywords: 4406 Human Geography; 40 Engineering; 44 Human Society; 7 Affordable and Clean Energy; 13 Climate Action; aviation decarbonisation; hydrogen-powered aircraft; feasibility constraint; airside operation; net-zero aircraft